Pengaruh Penggunaan Masker Kulit Buah Manggis Pada Kulit Wajah Berjerawat - Zahrah, Azizah; Rifanda, Firara; Rosalinda, Linda; Saputra, Indra (Universitas Negeri Jakarta, 2024)
Mask is a cosmetic preparation used on the face to get a tightening and cleaning effect from dirt attached. Mangosteen peel which chemically contains xanthones as active chemicals that are antioxidants that can replace the function of chemical drugs to overcome acne on the face. This study aims to find out about the effect of using mangosteen peel masks on the healing results of acne on acne-prone facial skin. The research method used in this study is a quasi-experimental method (pseudo-experiment). The data collection methods used are observation, interviews, and experiments. The data analysis technique used is descriptive statistics. The results of the research on making masks have a smooth texture in accordance with the texture of masks in general, a fairly distinctive smell, attractive colors or pigmentation, appropriate and good adhesion and stick to the face and hands, so that the mask is liked by all panelists who have been tested as many as 14 panelists.